1985
DOI: 10.1159/000199249
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Verapamil on Gastric Acid Secretion and Gastrin Release in Dogs

Abstract: Gastric secretion is supposed to be calcium-dependent. The effect of verapamil (0.3 mg/kg/h i.v.), a calcium channel-blocking agent, on stimulated gastric acid secretion and gastrin release was investigated in 8 mongrel dogs. Stimulation was either performed by bombesin (1.0 μg/kg/h i.v.) or by insulin (0.3 U/kg i.v.). Verapamil significantly inhibited both the bombesin- and the insulin-stimulated gastric acid secretion. Mean total gastric acid output over a 120-min period was 9.5 ± (SEM) 2.2mmol after bombesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In dogs, verapamil given i.v. inhibited bombesin-stimulated acid secretion [16] and in another study, verapamil was able to reverse serotonininduced jejunal secretion of water and electrolytes [29]. The authors, therefore, suggested that calcium-channel blockers might be promising as therapeutic agents in serotonin-induced intestinal secretion due to carcinoid syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…In dogs, verapamil given i.v. inhibited bombesin-stimulated acid secretion [16] and in another study, verapamil was able to reverse serotonininduced jejunal secretion of water and electrolytes [29]. The authors, therefore, suggested that calcium-channel blockers might be promising as therapeutic agents in serotonin-induced intestinal secretion due to carcinoid syndrome.…”
Section: Discussionmentioning
confidence: 97%